Meta-skepticism - Pérez Chico, David; Sanfélix Vidarte, Vicente (Estudios de Filosofía, 2019)
In the present article we subscribe to a form of meta-skepticism according to which the theory of knowledge is impossible. This form of meta-skepticism is based on two apparently necessary conditions: (1) the identification of one or more of the assumptions of the theory of knowledge in order to criticize them; and (2) the more or less explicit assumption that there is an alternative account of knowledge to the one attributed to the theory of knowledge in question. Once these preliminary issues have been clarified, we will review different varieties of meta-skepticism in order to verify whether all of them, even the most austere, satisfy the previous two conditions. This will lead us to conclude, in the first place, that all varieties of meta-skepticism satisfy them and, secondly, that no type of meta-skepticism is free of epistemological implications. In the light of this conclusion, we will end up considering whether meta-skepticism stands its ground.